Baseline data to characterize and manage the small-scale fishery (SSF) of an oncoming Marine Protected Area (Cape Milazzo, Italy) in the western Mediterranean Sea. (1st November 2017) - Battaglia, Pietro; Andaloro, Franco; Consoli, Pierpaolo; Pedà, Cristina; Raicevich, Saša; Spagnolo, Massimo; Romeo, Teresa
Abstract: This study characterizes the small-scale fishery (SSF) of the oncoming Italian Marine Protected Area of Cape Milazzo in the western Mediterranean Sea and describes the recent evolution of SSF activities in the study area during recent years. Data on fishing activities, catch and effort were collected in 2006–2007 and 2014 and then compared. Information on fishermen perceptions about local fishery management and conflicts were collected by a questionnaire survey relating fisheries policies and regulations during 2012–2013. A substantial reduction of fleet (−27.5% of vessels) was recorded between the 2006–2007 and 2014. The use of fishing gears varied during season depending on fishing tactics, meteorological conditions and resource availability, particularly in the case of gregarious fish, as revealed by statistical analysis (e.g., small tunas, carangids and mackerels). A general increase in hake and cuttlefish CPUE during 2014 was recorded. However, the study highlighted a suffering status for local SSF, due to both the difficulty to apply a growing amount of rules and prohibitions and the conflicts with illegal and recreational fishing. The establishment of a Local Management Plan (LMP) in the area has been the first step for increasing the fight against illegal fishing as well as the management of fishing grounds. Furthermore, the establishment of a new MPA should take into account these results in order to develop appropriate management measures for environmental protection, also allowing for the maintenance of biologic, social and economic sustainability of artisanal fishing activities. Highlights: A reduction of fleet was recorded between the 2006–2007 and 2014. Gear use varied depending on fishing tactics, weather and resource availability. A growing amount of rules and prohibitions determines a suffering status for SSF. Conflicts between SSF and illegal and recreational fishing were detected. These data will be useful to develop appropriate management strategies.